Evaluación del control de inventario de la empresa MIDISPRO S.A. - Guamán Criollo, Liliana Elizabeth (2021)
This research work takes place in the city of Babahoyo, being the place where the headquarters of the company Midispro S.A. is located, which has more than ten years of experience in the market of the province of Los Ríos. Like any commercial company, it is important for you to keep an inventory control to be able to know the situation you are in and take the respective necessary measures at the right time. In such a way that surveys were carried out to determine the control that is being carried out and how it affects the different findings within the inventories. Identifying that the products should be classified in ABC to keep a better control and avoid having economic losses due to expired, obsolete products.